Comparison of total intravenous anesthesia and inhalational anesthesia in patients undergoing liver surgery: a systematic review and meta-analysis - Gustavo R.M. Wegner; Bruno F.M. Wegner; Henrik G. Oliveira; Luis A. Costa; Luigi W. Spagnol; Valentine W. Spagnol; Jorge R.M. Carlotto; Eugénio Pagnussatt Neto (Brazilian Journal of Anesthesiology)
Background: The impact of choosing between inhalational anesthetics and propofol for maintenance anesthesia in liver transplantation or liver resections remains uncertain. Methods: A systematic search was conducted on PubMed, Scopus, Embase, Web of Science, and the Cochrane Library on September 5, 2023, adhering to the Cochrane Handbook and PRISMA guidelines. Results: Fifteen randomized controlled trials and five observational studies, comprising 1,602 patients, were included. The statistical analysis was categorized into three groups: liver transplantation (four studies), living donor hepatectomy (four studies), and liver mass hepatectomy (twelve studies). The liver mass hepatectomy group was further subdivided based on the performance of the Pringle maneuver and the use of pharmacological preconditioning. Statistically significant results are described below. In liver transplant recipients, propofol anesthesia was associated with lower AST levels on the first postoperative day. Hepatic donors anesthetized with propofol had higher total infusion volumes and intraoperative urine output. Patients undergoing liver mass resection with the Pringle maneuver and propofol anesthesia had higher peak AST and ALT levels compared to those who received pharmacological preconditioning. Patients undergoing liver mass resection with the Pringle maneuver and propofol anesthesia had higher AST and ALT levels on both the first and third postoperative days, increased total infusion volumes, and shorter hospital stays, when compared to pharmacological conditioning. Conclusions: Our findings do not offer sufficient evidence to inform clinical practice. The choice between propofol-based and inhalational anesthesia should be tailored to the individual patient's condition and the nature of the procedure being performed. Registration: PROSPERO ID: CRD42023460715.